Pancreatic cancer intrinsic PI3Kα activity accelerates metastasis and rewires macrophage component - Benoit Thibault; Fernanda Ramos‐Delgado; Elvire Pons‐Tostivint; Nicole Therville; Celia Cintas; Silvia Arcucci; Stephanie Cassant‐Sourdy; Gabriela Reyes‐Castellanos; Marie Tosolini; Amelie V Villard; Coralie Cayron; Romain Baer; et al. (EMBO Molecular Medicine)
Abstract Pancreatic ductal adenocarcinoma (PDAC) patients frequently suffer from undetected micro‐metastatic disease. This clinical situation would greatly benefit from additional investigation. Therefore, we set out to identify key signalling events that drive metastatic evolution from the pancreas. We searched for a gene signature that discriminate localised PDAC from confirmed metastatic PDAC and devised a preclinical protocol using circulating cell‐free DNA (cfDNA) as an early biomarker of micro‐metastatic disease to validate the identification of key signalling events. An unbiased approach identified, amongst actionable markers of disease progression, the PI3K pathway and a distinctive PI3Kα activation signature as predictive of PDAC aggressiveness and prognosis. Pharmacological or tumour‐restricted genetic PI3Kα‐selective inhibition prevented macro‐metastatic evolution by hindering tumoural cell migratory behaviour independently of genetic alterations. We found that PI3Kα inhibition altered the quantity and the species composition of the produced lipid second messenger PIP3, with a selective decrease of C36:2 PI‐3,4,5‐P3. Tumoural PI3Kα inactivation prevented the accumulation of pro‐tumoural CD206‐positive macrophages in the tumour‐adjacent tissue. Tumour cell‐intrinsic PI3Kα promotes pro‐metastatic features that could be pharmacologically targeted to delay macro‐metastatic evolution.